NURSE READINESS TO PERFORM CARDIOPULMONARY RESUSCITATION DURING COVID 19 PANDEMIC - Rita Kombong; Tri Nurmaningsih Hatala (Jurnal Ilmu Keperawatan Medikal Bedah, 2021)
Coronavirus Disease 2019 (Covid 19) has become a global pandemic with rapid spread, resulting in an increase in the number of cases of illness and death, which is the responsibility of health workers, particularly nurses on the front lines. Nurses, on the other hand, are extremely vulnerable to transmission despite wearing personal protective equipment. This treatment necessitates planning, including the readiness of nurses to provide services, especially for critical patients (cardiac arrest) requiring cardiopulmonary resuscitation (CPR). Preparedness can reduce transmission to nurses by paying attention to standard cardiopulmonary resuscitation procedures in the pandemic era. The purpose of this study was to determine the preparedness of nurses to perform cardiopulmonary resuscitation based on their knowledge, attitudes, and skills during the Covid 19 pandemic era at dr. M Haulussy Hospital Ambon. A quantitative analytical study approach was used in this study, with a cross-sectional study design. The total number of samples in this study was 33, and the sampling technique used was Total Sampling. The results showed there was readiness with a p-value < (0.05), knowledge with a value of 0.660, attitude with a value of 0.559, and CPR skills of 1.000. The conclusion is that a nurse is well-prepared in terms of knowledge, attitudes, and skills. It is hoped that it will be useful to the hospital in developing plans and nursing interventions in overcoming this pandemic. Keywords: readiness, cardiopulmonary resuscitation, COVID 19, nurse.